Symposium 5: A Proposed Institutional Approach to Designing for Networked Learning at the Course Level - Eberhard, Sally; Chanane, Nawal; Nguyen, Nhung; Kehrwald, Benjamin A.; Winters, Annemie; Sim, Kwong Nui (Proceedings of the International Conference on Networked Learning, 2024)
This conceptual paper proposes a design approach for implementing networked learning at a course level at a University in New Zealand (Aotearoa). Networked learning has been noted to have many benefits for learners in the growing body of literature. However, the principles could be implemented differently depending on the institutional context, strategic goals and current practices. The objective of this paper is to propose an institutional approach to design for networked learning at the course level. The implementation approach should be systematic not uniform. This paper outlines the institutional context and rationale, evaluates each of the eight principles of networked learning to institutional context and suggests implementation ideas. A tiered approach to implementing design for networked learning at a course level is proposed, along with future work needed for the implementation across our institution.